Management information system : for BBA fourth semester of WBUT - Jindal, Aman (Kalyani Pub, 2011)
Management information system : for BBA fourth semester of WBUT / Jindal, Aman. -- Kolkata: Kalyani Pub., 2011 658.403 J61e2 2nd rev. ed. No. of Copies : 1